Chiral Acyl Radicals Generated by Visible Light Enable Stereoselective Access to 3,3-Disubstituted Oxindoles: Application toward the Synthesis of (–)- and (+)-Physovenine - Späth, Josef; Oddy, Meghan J.; Hunter, Roger; Petersen, Wade F. (Synthesis, 2022)
Exploration of the repurposing of N-acyl chiral auxiliaries for use as novel chiral C1 radical synthons is reported. The acyl radicals are generated under visible-light-mediated single-electron transfer of N-hydroxyphthalimido ester, and their use toward the stereoselective synthesis of 3,3-disubstituted oxindoles via a radical addition–cyclisation sequence is demonstrated. The downstream synthetic utility of this method is showcased in the formal synthesis of the natural product (–)-physovenine. TEMPO trapping experiments support the proposed reaction mechanism.
Keywords: photocatalysis; acyl radicals; C–H functionalisation; oxindoles; natural products; stereoselective synthesis